Resenha de FAIRCLOUGH, Norman; FAIRCLOUGH, Isabela. Political discourse analysis: a method for advanced students. London: Routledge, 2012. - Rodrigues, Emmanuel Henrique Souza; Rodrigues, Emmanuel Henrique Souza (Cadernos de Linguagem e Sociedade, 2017)
Resenha de FAIRCLOUGH, Norman; FAIRCLOUGH, Isabela. Political discourse analysis: a method for advanced students. London: Routledge, 2012.